2013
DOI: 10.1007/s10286-013-0193-y
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying in postural tachycardia syndrome: a preliminary report

Abstract: Purpose Autonomic neuropathy is widely recognized to be associated with upper gastrointestinal symptoms and abnormal (i.e., rapid or slow) gastric emptying. While patients with postural orthostatic tachycardia syndrome (POTS) may also have gastrointestinal symptoms, our understanding of gastric emptying disturbances in POTS is very limited. The objectives of this study were to evaluate the relationship between gastric emptying disturbances and gastrointestinal symptoms in patients with POTS. Methods . We ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 32 publications
1
37
0
1
Order By: Relevance
“…Of note, abnormalities in GI motility provoke symptoms such as early satiety, nausea, bloating, and abdominal pain [30]. Four of these studies that describe the GI symptoms in POTS also reported evidence of abnormal gastric motility- either rapid gastric emptying (43%) or delayed gastric emptying (gastroparesis, 20%) [5, 36, 48, 67]. …”
Section: Resultsmentioning
confidence: 99%
“…Of note, abnormalities in GI motility provoke symptoms such as early satiety, nausea, bloating, and abdominal pain [30]. Four of these studies that describe the GI symptoms in POTS also reported evidence of abnormal gastric motility- either rapid gastric emptying (43%) or delayed gastric emptying (gastroparesis, 20%) [5, 36, 48, 67]. …”
Section: Resultsmentioning
confidence: 99%
“…12 Multi-Ethnic Study of Atherosclerosis utilized an exponential survival model to estimate the arterial age as a function of CAC. 13 The same research group has published a method of calculating CAC by age- and gender-matched percentile rank.…”
Section: Methodsmentioning
confidence: 99%
“…Electrical activity of the stomach has been shown to change during upright position in children with POTS, and both increased and decreased gastric emptying has been noted as well (16,17). Functional gastrointestinal disorders, such as irritable bowel syndrome and functional dyspepsia, are also associated with POTS, suggesting the possibility that increased variability of the gastric pacemaker rhythm and sympathetic nervous system dysfunction in POTS can directly disturb gastrointestinal function (18).…”
Section: Discussionmentioning
confidence: 99%